Pengaruh Work Place Well-Being dan Mental Health terhadap Kinerja Karyawan melalui Motivasi Kerja sebagai Variabel Moderating pada Karyawan Bulog Jastasma Kanwil Sulselbar - Nita asmara; Suhartini, Eka; Amir, Amir (Study of Scientific and Behavioral Management (SSBM), 2024)
This study aims to determine the effect of work place well-being and mental health on employee performance through work motivation as a moderating variable at Bulog Jastasma Kanwil Sulselbar. In this study, the variables used are work place well-being and mental health as independent variables, performance as the dependent variable, and work motivation as a moderating variable. This research is a quantitative study. The data source used in this study is primary data collected through a survey using a questionnaire. The method of calculating the number of samples using the Slovin formula and the sampling method using the probability sampling technique, so that the number of samples used is 100 people. The data is processed using the Patrial Least Squares (PLS) method and applied using Smart PLS 4. The results of this study indicate that work place well-being has a positive and significant effect on employee performance, mental health has a positive and significant effect on employee performance, work place well-being has a negative and significant effect on employee performance moderated by work motivation, and mental health has a negative and insignificant effect on employee performance moderated by work motivation. Keywords: Work Place Well-Being, Mental Health, Employee Performance, Work Motivation